2022
DOI: 10.1186/s12951-022-01253-8
|View full text |Cite
|
Sign up to set email alerts
|

In-situ TiO2-x decoration of titanium carbide MXene for photo/sono-responsive antitumor theranostics

Abstract: Background Sonodynamic therapy (SDT) has emerged as a noninvasive therapeutic modality that involves sonosensitizers and low-intensity ultrasound. However, owing to the rapid recombination of charge carriers, most of the sonosensitizers triggered poor reactive oxygen species (ROS) generation, resulting in unsatisfactory sonodynamic therapeutic effects. Results Herein, a photo/sono-responsive nanoplatform was developed through the in-situ systhesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 63 publications
1
36
0
2
Order By: Relevance
“…In response to H 2 O 2 overproduction, the sonosensitizer TiO 2 is in situ generated in Ti 3 C 2 MXene to form TiO 2 /Ti 3 C 2 nanosheets. Due to the excellent electrical conductivity of the carbon matrix, , the separation of electrons (e – ) and holes (h + ) is promoted under US irradiation. Simultaneously, the cavitation effect of US could enhance the chemodynamic process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to H 2 O 2 overproduction, the sonosensitizer TiO 2 is in situ generated in Ti 3 C 2 MXene to form TiO 2 /Ti 3 C 2 nanosheets. Due to the excellent electrical conductivity of the carbon matrix, , the separation of electrons (e – ) and holes (h + ) is promoted under US irradiation. Simultaneously, the cavitation effect of US could enhance the chemodynamic process.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the promising biomedical characteristics, 2D MXenes (titanium carbide, Ti 3 C 2 ) have been utilized as delivery platforms to load different types of sonosensitizer for enhancing the synergistic effect of the photothermal-sonodynamic therapeutic. 24,25 To our knowledge, the utilization of the physicochemical properties of Ti 3 C 2 to in situ generate sonosensitizers for SDT has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Versus PTX and NIR-triggered PPSiI, O 2 -PPSiI under NIR laser irradiation showed more high-efficiency ROS and 1 O 2 generation in solution and MDA-MB-231 cells (Additional file 1 : Fig. S15), indicating an important role of O 2 release in the production of 1 O 2 and ROS [ 50 , 51 ]. Subsequently, the in vivo synergistic antitumor effect of the NIR-triggered O 2 -PPSiI nanosystem was further investigated with MDA-MB-231-bearing nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the application of MXene alone in one area of treatment or diagnosis, researchers are more interested in developing its effective synergistic therapeutic effects with multiple treatment modalities. Combining PTT and PDT with other therapeutic diagnostic modalities synergistically can often produce unexpected results, such as combining PTT with PDT [ 165 ], PTT with SDT [ 166 ] or PTT with conventional chemotherapy and PDT or PTT with drug delivery [ 167 ]. Qun et al found that the synergistic effect of Mo 2 C-mediated PDT/PTT (induction of apoptosis) was significantly better than that of PDT or PTT alone by using the ROS buster NaN 3 to eradicate ROSs and using Mo 2 C-mediated phototherapy in an ice bath to eliminate the effects of PDT and PTT [ 157 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%